Effects of ibogaine per os application on redox homeostasis in rat liver and erythrocytes - Vidonja Uzelac, Teodora; Tatalović, Nikola; Mijović, Milica; Koželj, Gordana; Nikolić Kokić, Aleksandra; Oreščanin Dušić, Zorana; Bresjanac, Mara; Blagojević, Duško (Archives of Biological Sciences, 2019)
Paper description: Ibogaine, administered as a single oral dose (1-25 mg/kg body weight) is used as an addiction-interrupting agent. We examined the in vivo effect of a single per os dose of ibogaine (1 or 20 mg/kg) on hepatic and erythrocyte antioxidant defenses after 6 and 24 h. Ibogaine increased overall energy consumption, estimated by the level of liver glycogen. Ibogaine had no effect on antioxidant defense but increased TBARS concentration, pointing to mild hepatic oxidative stress. Abstract: Ibogaine, administered as a single oral dose (1-25 mg/kg body weight), has been used as an addiction-interrupting agent. Its effects persist for up to 72 h. Ex vivo results showed that ibogaine induced cellular energy consumption and restitution, followed by increased reactive oxygen species production and antioxidant activity. Therefore, the aim of this work was to explore the effect of a single oral dose of ibogaine (1 or 20 mg/kg body weight) on antioxidative defenses in rat liver and erythrocytes. Six and 24 h after ibogaine administration, histological examination showed glycogenolytic activity in hepatocytes, which was highest after 24 h in animals that received 20 mg/kg ibogaine. There were no changes in the activities of superoxide dismutases, catalase, glutathione peroxidase, glutathione reductase and glutathione-S-transferase in the liver and erythrocytes after ibogaine treatment, regardless of the dose. Hepatic xanthine oxidase activity was elevated in rats that received 20 mg/kg compared to the controls (p<0.01), suggesting faster adenosine turnover. TBARS concentration was elevated in the group treated with 1 mg/kg after 24 h compared to the controls (p<0.01), suggesting mild oxidative stress. Our results show that ibogaine treatment influenced hepatic redox homeostasis, but not sufficiently to remodel antioxidant enzyme activities at 6 and 24 h post-ibogaine application. https://doi.org/10.2298/ABS180918055V Received: September 18, 2018; Revised: November 28, 2018; Accepted: 2018; Published online: December 6; 2018 How to cite this article: Vidonja-Uzelac T, Tatalović N, Mijović M, Koželj G, Nikolić-Kokić A, Oreščanin-Dušić Z, Bresjanac M, Blagojević D. Effects of ibogaine per os application on redox homeostasis in rat liver and erythrocytes. Arch Biol Sci. 2019;71(1):133-44.